Legal Protection of Children Outside of Marriage Perspective of Khi and the Child Protection Law (Study in Sukajadi, Punggur, Central Lampung) - Rijala Sholeh, Muhammad; Arsyad, Mufid (Jurnal Mahkamah : Kajian Ilmu Hukum dan Hukum Islam, 2024)
The phenomenon of child births outside of legal marriage is increasing and causing legal and social problems, especially related to legal status, societal stigma, and the fulfillment of children's rights. The difference in regulation between the Compilation of Islamic Law (KHI) and positive law also affects the effectiveness of legal protection for children out of wedlock. This study aims to analyze the legal protection of children out of wedlock from the perspective of KHI and the Child Protection Law, as well as assess its implementation and effectiveness in Sukajadi Village, Punggur District, Central Lampung Regency. This study uses a qualitative method with an empirical and juridical-sociological approach. Data were obtained through observation, interviews, and documentation, then analyzed using Miles and Huberman's interactive model. The results of the study show that legal protection for children out of wedlock is not optimal. Administratively, the registration of children's identities is still oriented towards formal provisions so that the name of the biological father cannot be included without legal determination. In the perspective of Islamic law, children only have a nasab relationship with the mother, while positive law provides space for the recognition of civil relations with the biological father. However, its implementation is constrained by economic factors, complex legal procedures, and low public understanding, creating a gap between legal norms and practices in the field.